PENGEMBANGAN ARDUINO DATA LOGGER MENGGUNAKAN TDR H3CR UNTUK SIMULATOR PASANG SURUT - Anugrah, Maulana; Kusuma, Hollanda Arief; Putra, Riandra (Program Vokasi-Universitas Negeri Gorontalo, 2024)
Tides, crucial natural phenomena, significantly impact various aspects of life. Recognizing their importance, this study presents the development of a tidal simulator leveraging Arduino data logging and TDR H3CR technology. The simulator aims to mimic tidal processes, crucial for educational and research purposes. Traditional methods of acquiring tidal data are time-consuming and expensive. Thus, a simulator proves advantageous in reducing research time and costs. At Raja Ali Haji Maritime University, a tidal simulation model exists but with manual operation and limited data capture capabilities. To address these limitations, this study designed a new simulator utilizing H3CR, DC Water Pump, and DC Selenoid Valve for automated tidal circulation. The research method involved system design, component integration, and laboratory experiments. Calibration of components like the ultrasonic sensor HC-SR04 ensured accurate data collection. The overall system experiment validated the simulator's functionality, demonstrating its ability to replicate tidal processes effectively. Results indicated that the simulator produced tidal patterns resembling sinusoidal waves, with slight noise attributed to sensor limitations. The designed simulator serves as an efficient learning tool for understanding tidal phenomena, exhibiting comparable results to natural tidal data. This study contributes to the advancement of tidal simulation technology, offering a cost-effective and accessible solution for educational and research purposes.